Facile Synthesis and Structural Characterization of Co3O4 Nanocubes - Min Kang; Hai Zhou (AIMS Materials Science, 2015)
Co3O4 nanocubes were synthesized via a simple hydrothermal method. X-ray diffraction (XRD) and high-resolution transmission electron microscopy (HRTEM) analysis revealed that the product was cubic single crystal Co3O4, with the width of several ten nanometers to several hundred nanometers. The influence of reaction temperature and the amount of dispersant on the size and morphology of the as-obtained Co3O4 were investigated. On the basis of condition-dependent experiments, a possible aggregate-dissolution-recrystallization growth mechanism was proposed to explain the formation process of the Co3O4 nanocubes. The catalytic activity characterization showed that the as-prepared Co3O4 nanocubes can catalyze the thermal decomposition of ammonium perchlorate (AP) effectively.